Geographic information system for micro-level decision making in the agriculture sector of central midlands of Kerala - Anup Balakrishnan (Department of Soil Science and Agriculture Chemistry, College of Horticulture, 2005)
The present study was carried out in the Centre for Land Resources Research and Management, Department of Soil Science and Agricultural Chemistry, College of Horticulture, Kerala Agricultural University, Thrissur during the period 2001 to 2004 with the broad objective of integrating available data on the land and agricultural resources of Madakkathara Panchayat into a Geographic Information System (GIS) and to demonstrate the capability of GIS as a decision support system to design projects for integrated resource management.